TRENDS IN OBESITY TREATMENT: A REVIEW OF THE LITERATURE FROM THE LAST SIX YEARS - Adam Sobiński; Aleksandra Sadowska; Aleksandra Welkier; Joanna Miśkiewicz; Aleksandra Dudek; Patrycja Pietrusińska; Jakub Moder; Anna Dziewierz; Paula Kwaśniewska; Patrycja Śliwa-Tytko (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Obesity is a major health and economic issue, increasing the risk of type 2 diabetes, hypertension, and cardiovascular diseases. This review analyzes recent advances in obesity treatment, focusing on pharmacotherapy, surgical techniques, minimally invasive methods, and psychotherapy. Materials and Methods: This review included publications from 2018 to 2024 available in the PubMed and Google Scholar databases. The analysis focused on the efficacy and safety of various therapeutic interventions, including modern pharmacological agents, surgical procedures, the use of intragastric balloons, and psychotherapies such as Cognitive Behavioral Therapy (CBT) and Acceptance and Commitment Therapy (ACT). Results: New pharmacotherapies, such as semaglutide and tirzepatide, lead to 15–25% weight loss. Surgical techniques like Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) achieve 27–69% excess weight loss (EWL). Intragastric balloons provide a temporary 12–25% EWL. CBT effectively supports weight loss, enhances quality of life, and promotes long-term behavioral changes. Conclusions: In conclusion, optimal obesity management requires a multifaceted approach that considers the patient’s health status, comorbid conditions, and capacity for lasting lifestyle changes. The integration of pharmacological and surgical interventions with psychotherapeutic methods such as CBT and ACT allows for a more holistic approach to addressing this complex health issue. Future research should focus on the long-term effectiveness of these methods and their synergy, which could contribute to the development of more personalized and effective treatment strategies.